THE HAPPINESS OF THE TRADITIONAL BOTI PEOPLE ON TIMOR ISLAND - Oki, Kamilaus Konstanse; Be, Emanuel (PT Inovasi Pratama Internasional, 2023)
The Boti tribe is an inland tribe on the Indonesian island of Timor. Socio-economic and cultural life is very unique from other tribes in the world. Traditional lifestyle by relying on nature and surroundings as a source of life. Relations and interactions with outside influences are also unique because they strictly protect themselves by avoiding advances in science, technology and factory production. The Boti tribal community believes that the entry of external influences in the form of providing health facilities, modern communication facilities, government assistance, manufactured products, national religion, science and technology and other forms of external influence are threats to the sustainability of traditions and culture. Subjectively, the Boti people are very happy with the socio-economic conditions of life as measured by the dimensions of feeling, the dimensions of satisfaction and the dimensions of the meaning of life. Happy in carrying out all activities. Forms of social violations in people's lives and other violations that have a legal impact are not found in interactions and are unlawful. If there are violations and repetitions, they will be evacuated from the Boti tribe as a severe punishment.